2018
DOI: 10.1177/0300060518770577
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided vacuum-assisted breast biopsy in the diagnosis of breast microcalcifications

Abstract: ObjectiveThe present study was performed to assess the accuracy and clinical value of image-guided vacuum-assisted breast biopsy in the diagnosis of mammography-detected breast microcalcifications.MethodsThis prospective study involved 100 patients with suspicious mammography-detected microcalcifications who underwent image-guided vacuum-assisted breast biopsies from January 2013 to October 2016. Stereotactic vacuum-assisted breast biopsy (SVAB) was performed in 64 patients, and ultrasound (US)-guided vacuum-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(38 reference statements)
2
13
0
Order By: Relevance
“…In our study, we found that the distribution of malignancies in BI-RADS category is similar with the standard guideline by American College of Radiology 16 . Our results corroborate with the findings of other studies which showed that the likelihood of malignancy increases with BI-RADS category 7,11,12,17,18 . Although calcifications play a crucial role in early breast cancer diagnosis, they are also associated with 63.2% of benign pathology 7 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, we found that the distribution of malignancies in BI-RADS category is similar with the standard guideline by American College of Radiology 16 . Our results corroborate with the findings of other studies which showed that the likelihood of malignancy increases with BI-RADS category 7,11,12,17,18 . Although calcifications play a crucial role in early breast cancer diagnosis, they are also associated with 63.2% of benign pathology 7 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results corroborate with the findings of other studies which showed that the likelihood of malignancy increases with BI-RADS category 7,11,12,17,18 . Although calcifications play a crucial role in early breast cancer diagnosis, they are also associated with 63.2% of benign pathology 7 . The prediction of benign or malignant calcifications are possible by following ACR BI-RADS mammography lexicon guidelines.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…22,23 Minimally invasive biopsy is not suitable for patients with small breast thickness and those whose nodules are close to the skin, because the breast skin is easily injured during the operation. 24 For patients who plan to breastfeed, minimally invasive biopsy of breast nodules should not be used in the area of the areola. Otherwise, it may cause tilting and retraction of the nipple and may increase the probability of acute mastitis during lactation.…”
Section: Aspects Of Clinical Application Of Ultrasound-guided Minimalmentioning
confidence: 99%